Strengthening Public Relations Practitioners' Capacity to Address Artificial Intelligence Challenges - Wulandari, Maulina Pia; Wachid, Ivan Bimantoro; Argyanti, Talitha; Sasela, Mirel Imelda; Zuhri, Mochamad Fernanda Abuzar; Jukiabtari, Serly Novita; Taqi, Naila (Universitas Serang Raya, 2025)
The emergence of digital tools like artificial intelligence (AI) presents unique challenges to public relations practices, making it crucial for practitioners to understand these dynamics and strengthen their competencies for the digital transformation era. A Community Service Team conducted a